(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Benmakhlouf Z, Benserradj O, Kellab R. 2022. Short Communication: Identification of phytochemical constituents of Syzygium aromaticum L. using gas chromatography coupled with mass spectrometry and evaluation of antimicrobial activity. Biodiversitas 23: 2586-2593. Syzygium aromaticum L. is a traditional spice that has various pharmacological activities attributed to its content of bioactive molecules. The purpose of this work is to evaluate phytochemical constituents of S. aromaticum L. extract using gas chromatography coupled spectrometry mass (CG/MS). The number detected of phenolic compounds was 45, which the most abundant being eugenol (54.63%), followed by Phenol,2-metoxy-4-(2-propenyl)-, acetate (eugenol acetate) (21.57%) and caryophyllene (16.71%). In addition, the antimicrobial activity was screened by the paper disc diffusion method for three bacterial strains, (Pseudomonas aeruginosa ATCC 27853, Salmonella sp. and Staphylococcus aureus 6538) and by the direct contact method on three fungal strains (Aspergillus niger, Aspergillus flavus and Candida albicans). The results showed that extract presents an inhibitory activity with all the strains tested. Salmonella sp. is very sensitive (++) to the stock solution (100mg/ml), sensitive (+) to dilutions (50 and 25) mg/ml with inhibition diameters of (16, 12, 10) mm respectively. The other bacterial strains are sensitive (+) only to the stock solution. The results of our experiment confirm that fungi strains: A. niger, A. flavus and C. albicans show a remarkable antifungal activity at 100mg/ml. The result indicated that the extract obtained from dried buds of S. aromaticum could be considered an agent for antibacterial and antifungal in the pharmaceutical field.